Are psychotic-like experiences related to a discontinuation of cannabis consumption in young adults? - Daedelow, Laura S.; Banaschewski, Tobias; Berning, Moritz; Bokde, Arun L. W.; Brühl, Rüdiger; Burke Quinlan, Erin; Curran, H. Valerie; Desrivières, Sylvane; Flor, Herta; Grigis, Antoine; Garavan, Hugh; Hardon, Anita; et al. (Schizophrenia research, 2021)
Objective - To assess changes in cannabis use in young adults as a function of psychotic-like experiences. - Method - Participants were initially recruited at age 14 in high schools for the longitudinal IMAGEN study. All measures presented here were assessed at follow-ups at age 19 and at age 22, respectively. Perceived stress was only assessed once at age 22. Ever users of cannabis (N = 552) gave qualitative and quantitative information on cannabis use and psychotic-like experiences using the Community Assessment of Psychic Experiences (CAPE). Of those, nearly all n = 549 reported to have experienced at least one psychotic experience of any form at age 19. - Results - Mean cannabis use increased from age 19 to 22 and age of first use of cannabis was positively associated with a change in cannabis use between the two time points. Change in cannabis use was not significantly associated with psychotic-like experiences at age 19 or 22. In exploratory analysis, we observed a positive association between perceived stress and the experience of psychotic experiences at age 22. - Conclusion - Age of first use of cannabis influenced trajectories of young cannabis users with later onset leading to higher increase, whereas the frequency of psychotic-like experiences was not associated with a change in cannabis use. The observed association between perceived stress and psychotic-like experiences at age 22 emphasizes the importance of stress experiences in developing psychosis independent of cannabis use.